mRNA melanoma vaccine revolution spurred by the COVID-19 pandemic - Xu, Ziyang; Fisher, David E. (Frontiers in Immunology, 2023)
The advent of mRNA vaccines represents a significant advance in the field of vaccinology. While several vaccine approaches (mRNA, DNA, recombinant protein, and viral-vectored vaccines) had been investigated at the start of the COVID-19 pandemic, mRNA vaccines quickly gained popularity due to superior immunogenicity at a low dose, strong safety/ tolerability profiles, and the possibility of rapid vaccine mass manufacturing and deployment to rural regions. In addition to inducing protective neutralizing antibody responses, mRNA vaccines can also elicit high-magnitude cytotoxic T-cell responses comparable to natural viral infections; thereby, drawing significant interest from cancer immunotherapy experts. This mini-review will highlight key developmental milestones and lessons we have learned from mRNA vaccines during the COVID-19 pandemic, with a specific emphasis on clinical trial data gathered so far for mRNA vaccines against melanoma and other forms of cancer.